Entre o dito e o feito : a garantia de permanência dos alunos no ensino fundamental nas escolas estaduais do município de Araras-SP - Zuttin, Marlene Aparecida da Silva (Universidade Federal de São Carlos, 2008)
This study aims at verifying the permanency of children and adolescents at public schools of the compulsory school system elementary school in the city of Araras. From the perspective of the right to education found in educational legislations in a confront between the legal and the real, the said and the done. Since the historical evolution of the educational rights in the Brazilian Constitutions from 1824 to 1988 and going through the Law for Directories and Bases, National Plan of Education, Underage Code and Statute for Children and Adolescents. Between the announced right and the guarantee of the right an incursion in the school environment occurs. This research takes a historical journey in the city of Araras since the conquests of backlands in São Paulo and presents its actors. The reality of the city is portrayed by using the index of social vulnerability for a better understanding of the economical and social aspects of its population. The study seeked to understand through official data, the approval, failure and abandonment, from the State Secretariat of Education São Paulo, the issue of permanency characterized and mapped in the eight selected public schools. The research brings the backstage between the imposed rules and the real daily routine of campus-schools with quantitative data from the State Secretariat of Education and qualitative data collected in interviews with people in charge of the selected schools. The project observed the movement of these indicators within the school itself contrasting it comparatively to another institution by organizing them in groups A and B of classified regions in different degrees of social vulnerability. The analysis took into consideration the organization of the elementary cycles I (1st to 4th grades) and II (5th to 8th grades) The study detected that the children and adolescents from group A located in areas of lesser social vulnerability have a longer permanency of their students which was proved in the indicators of approval, failure and abandonment. The children of the first cycle no matter the group A or B, presented better results of those indicators. Besides the official indicators, the research used interview with directors in order to get the interpretation and application of the legislation and educational concepts of daily school, specially, concerning to the access and the permanency of students in the school. The e index of social vulnerability has a very significant correlation with the results of permanency, because it embeds various social indicators among them such as levels of illiteracy, the householder s average number of years studied and income capable of reflecting the valuing of education and school by the families with influence on a good school performance. The complexity of the issue of the permanency cannot be explicated by an isolated factor. There are many variables that interfere and interrelate making difficult the isolation or an identification of a starting point in the process which keeps itself in a continuous and dialectic movement. Through the dissertation it has been observed that the issue of permanency of children and adolescents in the compulsory education goes far beyond the announced rights and the guarantees of the rights. The research has shown that the social conditions of these children and adolescents put them in excluding situations of all sorts and expropriate those who need to study.
Keywords: Educação; Ensino fundamental; Política educacional; Brasil - legislação - ensino; Exclusão social; Democracia; CIENCIAS HUMANAS::EDUCACAO